Evaluating the Dominance of Operating Systems in Mobile Computing: A Survey Approach - Nyme Ahmed; Syed Nafiul Shefat (International Journal of Computer and Information System (IJCIS), 2025)
Mobile computing revolves around the idea of being able to carry around your computer wherever you go. It is also known as the capacity to engage data and information without being at a certain physical place or network connection. The primary goal of mobile computing is to eliminate the requirement for a physical connection to send data. Mobile computing relies on software, hardware, and wireless communication. This research aims to provide a comprehensive review of mobile computing devices and operating systems from various papers. Essentially, it is a review paper in which most of the central operating systems are defined and compared in terms of security, market coverage, and customer satisfaction. In addition, the security issues, benefits, and limitations of mobile computing are also discussed in detail.